Pelaksanaan Kursus Pra Nikah Calon Pengantin Dalam Menggapai Keluarga Sakinah, Mawaddah Wa Rahmah Perspektif Pendidikan Agama Islam - Ima Damayanti; Sukhoiri (Syakhsiyah Jurnal Hukum Keluarga Islam, 2025)
Abstract: The purpose of this study is to examine in depth the implementation of premarital courses for prospective brides and grooms in achieving a sakinah, mawaddah wa rahmah family from the perspective of Islamic religious education. This research is a qualitative library study that uses books and other literature as the main objects analyzed through a descriptive-analytical approach. The results of the discussion reveal that there are several values of Islamic religious education in the premarital course for prospective brides and grooms, including i’tiqadiyah (faith-based values), ubudiyah (worship-related values), and khuluqiyah (moral values). These three values can be well understood by the prospective couples if supported by factors such as equality, deliberation, and awareness of each partner’s needs.   Keywords: Course. Bride and Groom. Islamic Religious Education.